PERANCANGAN BASIS DATA SISTEM PENENTUAN HARGA OPTIMAL DASTER DENGAN FUZZY LOGIC - Runtukahu, Winona Charisda; Trisnawarman, Dedi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Optimal pricing in the fashion industry can affect product competitiveness in the market such as sales levels and profits earned by the company. This research develops a web-based decision support system using the Fuzzy Logic method to determine the optimal price of negligee. The purpose of this research is to design and implement a decision support system that can help daster business actors in determining the optimal selling price. The research method used is based on the System Development Life Cycle (SDLC) with a prototyping model to develop a decision support system for analyzing the optimal pricing of daster products and analyzed using fuzzy logic methods to manage uncertainty and provide more flexible decisions based on existing data. Based on the research that has been done, it is concluded that the Fuzzy Logic-based Decision Support System (DSS) is an effective solution for managing these uncertainties, using linguistic variables such as “cheap”, “medium”, and “expensive”. As a result, this system is able to provide price recommendations that are evidence-based, fast, and responsive to market changes, thus helping businesses increase profitability and product competitiveness.